2008
DOI: 10.1007/s10530-008-9407-y
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of rats on the endangered native flora of French Polynesia (Pacific Islands): drivers of plant extinction or coup de grâce species?

Abstract: Although rats have clearly contributed to bird extinctions on islands, their role in plant extinctions is not as clear. Paleoenvironmental studies suggest rats were responsible for the demise of several island palm species. French Polynesia's islands provide an opportunity to evaluate ''modern'' impacts of rats on native flora. Our study shows that 15 threatened taxa (nine families) are damaged by rats. All 12 subjected to seed predation are woody plants with large-seeded drupes. Three experience severe predat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 28 publications
(19 reference statements)
5
68
0
1
Order By: Relevance
“…Past observations highlight the lack of ripe fruits on Lepidorrhachis plants unless mesh caging was applied to exclude rats from developing fruits (Moore 1966;Pickard 1980). The paucity of small juvenile plants in areas which have not been baited for rat control, both in our study plots and more generally throughout this unbaited area, supports the more general contention that the introduction of rats affects plant recruitment in a range of island ecosystems (Campbell and Atkinson 2002;Delgado García 2002;Towns et al 2006;Meyer and Butaud 2009;Traveset et al 2009). It is possible that rats also reduce seedling and juvenile growth as they have been observed eating palm leaf sheaths and causing leaf fall in both juvenile and adult palms consistent with similar damage observed on plants elsewhere (Traveset et al 2009).…”
Section: Discussionsupporting
confidence: 76%
“…Past observations highlight the lack of ripe fruits on Lepidorrhachis plants unless mesh caging was applied to exclude rats from developing fruits (Moore 1966;Pickard 1980). The paucity of small juvenile plants in areas which have not been baited for rat control, both in our study plots and more generally throughout this unbaited area, supports the more general contention that the introduction of rats affects plant recruitment in a range of island ecosystems (Campbell and Atkinson 2002;Delgado García 2002;Towns et al 2006;Meyer and Butaud 2009;Traveset et al 2009). It is possible that rats also reduce seedling and juvenile growth as they have been observed eating palm leaf sheaths and causing leaf fall in both juvenile and adult palms consistent with similar damage observed on plants elsewhere (Traveset et al 2009).…”
Section: Discussionsupporting
confidence: 76%
“…Yamashita et al (2003) suggested that R. rattus may be facilitating the invasion of the nonnative tree Bischofia javanica in the Ogasawara Islands because R. rattus depredates the seeds of the dominant native tree Elaeocarpus photiniae-folius both before dispersal (27% -33% of the seed crop) and after dispersal (41% -100%). Several other studies of fruit and seed removal have occurred on Pacific islands that include R. rattus as part of the rodent community, but the particular rodent species responsible for such removals were not identified (e.g., Moles and Drake 1999, Uowolo and Denslow 2008, Meyer and Butaud 2009, Erwin and Young 2010, GrantHoffman et al 2010, Chimera and Drake 2011.…”
Section: Impact On Plant Communitiesmentioning
confidence: 99%
“…All three simulated scenarios are broadly consistent with the major, undisputed paleoecological evidence: (i) the human population was decimated by the diseases introduced by Europeans after 1722 AD (Diamond, 2005;Hunt, 2007) and around 1850 AD the size of the population was between 1500 and 3000 individuals (Flenley and Bahn, 2003); (i) the rat population was large and peaked right after the arrival of the Polynesian settlers when palm seeds were very abundant and rats had a negative, although non-quantifiable, effect on tree growth (Steadman et al, 1994;Diamond, 2005;Hunt, 2007;Meyer and Butaud, 2008;Mieth and Bork, 2010), (iii) people substantially reduced the number of palm trees on the island and intensified agriculture over time (Flenley et al, 1991;Stevenson et al, 2006;Mann et al, 2008;Mieth and Bork, 2010;Ladefoged et al, 2013). Despite being all compatible with the above points, the three simulated scenarios reveal clear differences from one another in terms of human, rat, and palm tree population dynamics and, consequently, also in deforestation patterns.…”
Section: Discussionmentioning
confidence: 99%